Evaluation of Coping Strategies Adapted to Overcome Psychosocial Problems in Adults Residing at Residential Home: A Descriptive Study - A.L Mahalakshmi . (International Journal of Community Health Nursing And Practices, 2023)
Coping strategies refer to intentional actions taken to address and resolve personal or interpersonal challenges, aiming to manage, reduce, or tolerate stress or conflicts. Emotional-focused techniques specifically target the reduction of negative emotional responses caused by stressors. Some examples of coping strategies focused on emotions involve participating in activities to keep oneself busy and divert attention from stressors, seeking support, encouragement, empathy, and understanding from others. Objectives: (1) to assess the coping strategies adapted to overcome psycho social problem (2) to find the association between psycho social problem with the demographic variables and (3) to find the association between coping strategies with the demographic variables Design: Non experimental research design was selected for the study. Method: The researchers utilized a convenient sampling method to select the participants for the study. Data Collection Tool: checklist assessment for coping strategies adopted to overcome the psychosocial problem. Data Analysis: The collected data was subjected to analysis using descriptive and inferential statistical methods. Result: It showed that 40% of the them stated that stratified with my life 60% of the sample said that not satisfied with my life, 66.7% of the sample said that decreased my activity, 33.3% of the sample said that not decrease my activity, 43.3% of the sample said that my life is not emty, 56.7% of the sample sad that my life is empty, 73.3% of the sample said that life is bored, 26.7% of the sample said that not bored, 56.7% of the sample not hope about her future, 43.3% of the sample is hope about the future, 40 of the sample is bothered, 60% of the sample not bothered, 43.3% of the sample is having good sprit, 56.7% of he sample not have a good sprit, 34.3% is afraid something is going to happen, 66.7% of the sample not afraid, 53.7% of the sample not happy, 47.3% of the sample is feel happy, 40% is said feel helplessness, 60 feel not helplessness, 53.7% of the sample is feeling not restleeness, 43.3% of the sample said that feel restless, 40% of the sample is not worry about future, 60% of the ample worry about future, 66.7% of the sample said that worry about the past, 40% of the sample adopted music theraphy, 60% of the sample not adopted, 43.3% of the sample spent the time shopping, 56.7% of the sample spent the time watching tv, 90% of the sample adopted relaxation technique, 10% not adopted. The findings indicate a notable correlation between the psychosocial problem and demographic variables. Conclusion: Descriptive study on the assessment of coping strategies adapted to overcome psychosocial problem among adult residing at residential home. Data was gathered for analysis and was subsequently interpreted using statistical methods. Thus, the investigator was able to assess the coping strategies adopted to overcome the psychosocial problem.
Keywords: Coping strategies; emotional conflict; problem focused; stress